Absorption Properties from Microwire Composite and Films from Microwires and its Application to the Safety Control of Infrastructures (Global Journal of Science Frontier Research, 2021)
The properties of films made of shielding from a microwire composite and films made of shielding from parallel array of microwires have been studied in the distant diagnostics of dangerous deformations of critical infrastructure objects are investigate. Natural ferromagnetic resonance in glass-coated cast amorphous microwires reveals large residual stresses appearing in the microwire core during castingand external stresses. These stresses, together with magnetostriction, determine the magnetoelastic anisotropy. A correlation between the frequency of natural ferromagnetic resonance (NFMR) (0,1 to 12 GHz), determined from the dispersion of permeability, and alloy composition (or magnetostriction between 1 and 40 ppm) of glass-coated microwires has been systematically confirmed. Absorption of composite (microwire pieces embedded in a polymer matrix) screens has been experimentally investigated. Parallel theoretical studies suggest that a significant fraction of the absorption can be ascribed to a geometrical resonant effect, while a concentration effect is expected for the thinnest microwires. A wide absorption properties profile has been measured from 0.1 to 12 GHz, the form of this profile is ascribed to the presence of natural ferromagnetic resonance (NFMR) in cast glass-coated amorphous magnetic microwires.
Keywords: amorphousmagnetic microwires; ferromagnetic resonance; natural ferromagnetic resonance microwires